The Use of Blockchain Technology to Promote Energy Sustainability in Cities (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Inclusive and sustainable economic growth is a major challenge in today's digital age. Financial technology (FinTech) plays an important role in bridging the financial access gap while supporting environmental responsibility through the application of green finance. This study aims to analyse the role of FinTech in promoting inclusive economic growth and environmental sustainability, particularly through the application of blockchain technology in urban renewable energy systems. The research method uses a qualitative approach with secondary data analysis, supported by mathematical models to measure green financial inclusion and FinTech investment efficiency. The results show that the implementation of green FinTech significantly increases financial inclusion, expands economic access for the MSME sector, and reduces carbon emissions through investments in environmentally friendly energy projects. Global case studies in India and Sweden show that multisectoral collaboration and adaptive regulatory policies are key to creating a sustainable FinTech ecosystem. Therefore, the integration of technology, policy, and digital literacy among the public is necessary to realise digital finance that is fair, efficient, and oriented towards a green future